Strategic Management: A Bibliometric Mapping of Research Trends and Intellectual Structure - Judijanto, Loso; Muiz, Abdul (West Science Business and Management, 2026)
This study aims to map the research trends and intellectual structure of strategic management through a comprehensive bibliometric analysis. Data were collected from the Scopus database over a defined publication period and analyzed using VOSviewer to examine keyword co-occurrence, co-citation patterns, and thematic evolution. The findings reveal that strategic management research is structured around three major clusters: sustainability-oriented strategy, digital transformation and technological innovation, and human-centered and methodological approaches. The results indicate that sustainable development, decision making, and strategic approach are dominant themes, reflecting the growing importance of long-term value creation and adaptive strategy. Furthermore, emerging topics such as artificial intelligence, machine learning, and circular economy highlight the increasing role of technology and environmental concerns in shaping contemporary strategic management discourse. Temporal analysis shows a clear shift from traditional human-centered studies toward digitally enabled and sustainability-driven strategies. This study contributes to the literature by providing a systematic and visualized overview of the evolution of strategic management research, offering insights into current trends and potential future research directions.
Keywords: Strategic Management; Bibliometric Analysis; Research Trends; Intellectual Structure; Sustainable Development